A new curve-based approach to polyhedral machining - Jun, CS; Kim, DS; Park, S (ELSEVIER SCI LTD, 2002)
This paper presents a new approach to three-axis NC tool path generation for sculptured surfaces. In the proposed curve-based approach, the gouge-free tool paths are generated from a polyhedral model of the STL (stereolithography) format. The polyhedral model is offset by a local-offsetting scheme. Then, the offset elements such as triangular facets, trimmed cylinders, and trimmed spheres are sliced by a series of drive planes. The curve segments on a drive plane are sorted, trimmed and linked, while the concave gouge is removed during the trimming process. The method is implemented on a PC, and some illustrative examples are provided in this paper. The main advantage of the proposed method is that the tool path can be generated from a polyhedral model without any concave and convex gouge, especially on an NC machine that supports NURBS interpolation. Other advantages and disadvantages of the proposed model are also discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: TOOL-PATH GENERATION; CUTTER; SURFACES